Critical revision of Trichiales (Myxomycetes) at the Natural History Museum London (BM) - Moreno, G.; Castillo, A.; Thüs, H. (Phytotaxa, 2022)
Light and scanning electron microscopy were applied to re-assess diagnostic characters of type specimens and critical specimens of twelve species in the order Trichiales (Myxomycetes) from the collections of the Natural History Museum in London (BM). The results were used to discuss published data and the type status for specimens of Arcyria imperialis, Hemitrichia chrysospora, H. intorta, H. karstenii, H. leiotricha, Perichaena cornuvioides, Prototrichia metallica, Trichia affinis, T. intermedia, T. munda and T. scabra. We conclude that Hemitrichia karstenii and Trichia contorta are autonomous species, and we confirm the synonymy of Trichia intermedia with Trichia contorta. The transfer of Perichaena cornuvioides to the genera Trichia or Hemitrichia is rejected.